Small businesses, public health, and scientific integrity: whose interests does the Office of Advocacy at the small business administration serve? - USA. Center for Effective Government (Washington, DC, 2013)
"This report examines the activities of an independent office within the Small Business Administration: the Office of Advocacy. The Office of Advocacy has responsibility for ensuring that federal agencies evaluate the small business impacts of the rules they adopt. Scientific assessments are not “rules” and do not regulate small business, yet the Office of Advocacy decided to comment on technical, scientific assessments of the cancer risks of formaldehyde, styrene, and chromium. By its own admission, Advocacy lacks the scientific expertise to evaluate the merits of such assessments. The report analyzes correspondence and materials received through a Freedom of Information Act request made by staff at the Center for Effective Government. Our inquiry was driven by two questions: Why did the Office of Advocacy get involved in the debate over scientific assessments that do not regulate small business? Whose interests does the Office of Advocacy of the Small Business Administration actually serve? We found that the Office of Advocacy’s comments on these assessments raised no issues of specific concern to small business and relied almost exclusively on talking points provided by trade associations dominated by big chemical companies. Between 2005 and 2012, the American Chemistry Council (ACC) and its members spent over $333 million lobbying Congress and federal agencies on, among other things, a protracted campaign to prevent government agencies from designating formaldehyde, styrene, and chromium as carcinogens. The Formaldehyde Council, Styrene Industry Research Council, and Chrome Coalition spent millions more. These groups asked the Office of Advocacy for assistance, and the Office became their willing partner."